INHIBITORY EFFECT OF Sansevieria trifasciata L ON AERIAL PATHOGENIC MICROFUNGI IN TUTORIAL ROOMS - Sharah Julia Andayani; Amanah Amanah; Tissa Octavira Permatasari (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Air pollutants in a room can be caused by several things, such as microorganisms in the form of fungi. Fungi that dispersed in air with concentration>700 CFU/m3 can be categorized as air pollution which could lead to many symptoms of various human diseases An effort that may improve indoor air pollution is using anti pollutant plant such as Sansevieria trifasciata L. This study aims to determine the effectiveness of Sansevieria trifasciata L on the concentration of aerial pathogenic microfungi in the tutorial room in Faculty of Medicine Swadaya Gunung Jati University and identify the aerial pathogenic microfungi species in the tutorial room. Methods: This study was a quasi experimental research with pre and post-test group design. Eight tutorial rooms with 4 repetitions were tested for species microfungi growth using Saburoud Dextrose Agar (SDA) media in 32 petri discs. After 7 days of incubation, microfungi were identified and the colony form unit (CFU) number was counted. The data was analyzed using paired T test. Results: Ten aerial pathogenic microfungi growth were significantly (p = 0.000) inhibited by Sansevieria trifasciata L demonstrated by CFU number reduction from 54.18 – 204.94 CFU/m3 to 16.48 – 44.75 CFU/m3. Conclusions: Sansevieria trifasciata L effectively inhibited aerial pathogenic microfungi growth in tutorial rooms.